The attitude of Nigerian women to termination of pregnancies with major congenital anomalies - Enabudoso EJ; Akinmoladun JA (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2020)
Background: When couples are confronted with a pregnancy in which there is a major foetal anomaly, they have only two options: termination of the pregnancy or allowing the baby to be born. Objective: To determine the attitude of pregnant women in Nigeria to termination of pregnancies with major congenital anomalies. Methods: This is a descriptive study undertaken at two centres in Nigeria. Structured and pretested self-administered questionnaire was used for data collection including socio-demographics and attitude to termination of pregnancies with major congenital anomalies. Results: Three hundred and fifty-six pregnant women participated in the study. Most of the respondents were in the 21-40 years age group. More than half of the participants (236; 66.3%) agreed with the termination of pregnancies with major congenital anomalies and some of their reasons were "to prevent the baby from suffering" and "to prevent waste of resources". For the 120 (33.7%) who did not agree with termination of such pregnancies, some of their reasons were "to trust God for a miracle" and "hoping that God will not allow such" Conclusion: The findings from this study show that majority of the women were favourably disposed to the termination of pregnancies with major anomalies. However, women with such pregnancies need to be adequately counselled to be aware of the consequences of the decisions they make. Also, in a country where there are legal restrictions of abortion, efforts should be made to consider termination of pregnancies with major anomalies in the abortion laws.